2022
DOI: 10.1111/caim.12494
|View full text |Cite
|
Sign up to set email alerts
|

The role of open innovation hubs and perceived collective efficacy on individual behaviour in open innovation projects

Abstract: The effectiveness of a company's open innovation (OI) strategy strongly depends on the performance of the innovation projects it launches. However, OI research has dedicated only scant attention to the role played by the behaviour of individuals involved in these projects. This study focuses on the role played by an open innovation hub (OIH), an in‐house unit supporting and accelerating OI initiatives, and investigates how OIHs influence the innovative behaviour of employees involved in innovation projects. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…La encuesta (Chirico et al, 2022), (Miyao et al 2022, (Chi y Nan Lin, 2022, (Bashir et al, 2022) y (Amoroso et al, 2021) constituye unas de las técnicas más utilizadas por los investigadores que buscan analizar una amplia población, ya sea dentro de una empresa o en una determinada ubicación geográfica. Además, la utilización del análisis factorial, exploratorio y confirmatorio para evaluar la validez de constructo de todos los ítems pertenecientes a las encuestas.…”
Section: Metodologías De La Innovaciónunclassified
“…La encuesta (Chirico et al, 2022), (Miyao et al 2022, (Chi y Nan Lin, 2022, (Bashir et al, 2022) y (Amoroso et al, 2021) constituye unas de las técnicas más utilizadas por los investigadores que buscan analizar una amplia población, ya sea dentro de una empresa o en una determinada ubicación geográfica. Además, la utilización del análisis factorial, exploratorio y confirmatorio para evaluar la validez de constructo de todos los ítems pertenecientes a las encuestas.…”
Section: Metodologías De La Innovaciónunclassified
“…Over the past few decades, SCT has been widely used to explain different individual behaviors. Miyao Manabu et al [33] explored the influences of open innovation hubs and perceived collective efficacy on individual behavior. Mahdizadeh Seyed Mousa et al [34] applied it to predicting determinants of nosocomial infection control behaviors in hospital nursing staff.…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…Establishing a CIH contributes to innovation at the individual and organizational levels when an inclusive leadership is present. Furthermore, the hub can become a cultural-game-changing instrument for the organization since it fosters the innovative behavior of OI project members (Miyao et al, 2022).…”
Section: Corporate Innovation Hubsmentioning
confidence: 99%
“…In response to that call, a research stream suggested that innovation hubs are a means for a company to open its innovation processes (Kirschbaum, 2005;Kohler, 2016), but few consider the ecosystem management paradigm. For example, Miyao et al (2022) showed how a corporate solution for openness (like the Innovation Hub) affects individuals' innovative behaviors. While this helps to explain how Ptah and Thoth were successful in decentralizing the innovation culture and part of the hub processes, it does not consider ecosystem orchestration activities performed by the individuals.…”
Section: )mentioning
confidence: 99%